Acoustic feedback in high performance rowing training - Schaffert, N.; Mattes, K.; Effenberg, A. O. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Using sonification as acoustic feedback (AF) has effects on perception accuracy and regulation of movement patterns (Effenberg, 2005). Thus, it has become increasingly interesting in motor control and learning. To examine effects of AF on the mean boat velocity (vB), it was provided in technique training of elite rowers during the direct preparation phase for the World Championships. The investigation aimed at optimizing the boat run in on-water training. Methods: The German National Rowing Team (N=47) (juniors and seniors) was examined with the AF-system Sofirow in 12 boats (small and big boats). The boat acceleration (aB) was measured as effect variable with a MEMS-acceleration sensor (up to 125Hz, 1% measuring accuracy, ±2g measuring range). The aB-time trace was sonified (Parameter Mapping) and transmitted to athletes and coaches time synchronously during on-water training. Statistical analysis considered a minimum of 3 training sessions per boat in which AF was presented in blocks (with and without AF alternately). Standardized questionnaires examined AF s functionality and the athletes perception of it. Results: The analysis of variance showed a significant increase of the mean vB with AF compared to the reference section without AF for all boats (F2=15.85; p=0.00; .2p=0.45) and a significant interaction between the boats (F3=16.88; p=0.00; .2p=0.73). Intra-cyclical structure of the aB-time trace changed qualitatively. Replying to the questionnaires, AF was perceived as functional and supportive for the movement execution by providing a guiding function. Discussion: The results show the immediacy of AF to affect the mean vB in on-water rowing training of elite athletes as well as the potential to display characteristic phases of the rowing cycle (rc) by affecting its time-structure. AF drew athletes attention to the time-dynamic structure of rc which enables them to regulate its critical phases more precisely and supported the feeling for the movement execution. Moreover, synchronization and coordination among the athletes was improved. AF offers new possibilities to assist the technique training of elite rowers by providing feedback information via the sense of hearing and thus, to facilitate the development for a feeling of the rhythm in racing boats. AF has been integrated into the technique training of elite athletes in preparation for the Olympic Games.